Візантійські культурні впливи в побуті населення Давньої Русі - Сергєєва, М.С. (Археологія, 1992)
У статті розглядається процес сприймання і засвоєння візантійських елементів у давньоруській матеріальній культурі на побутовому рівні і виділяються його основні етапи. В работе рассматривается процесс освоения византийских элементов материальной культуры в Древней Руси на бытовом уровне.
Основные этапы этого процесса связаны с уровнем социально-экономического, культурного развития Руси и интенсивностью контактов. Появление византийских бытовых вещей способствует формированию традиции их употребления.
Официальное принятие христианства в конце X в. способствовало переориентации феодальных кругов на византийские ценности и знакомству с ними широких слоев населения. На протяжении XI — первой половины XIII в. на Русь поступают товары массового спроса и заимствуются некоторые элементы византийской культуры, которые не разрушив местных традиций вошли составной частью в древнерусскую бытовую культуру. The paper deals with the process of assimilation of Byzantian elements of material culture in the Ancient Rus at the every-day life level.
The main stages of the process are connected with a level of social-economical, cultural development of Rus and intensity of contacts. The appearance of Byzantian every-day life articles promotes formation of the tradition of their usage.
Official adoption of Christianity in the end of the 10th century promotes reorientation of feudal circles on Byzantian values and equaintance of the various strata of society with them. During the 11th - early 13th centuries consumer goods came to Rus and certain elements of the Byzantian culture are borrowed which became a part of the Ancient Rus every-day life culture without disturbing local traditions.